Hubungan Antara Persepsi Terhadap Gaji Dengan Loyalitas Kerja Pada Karyawan PT. Djitoe Indonesian Tbk. Surakarta - Pratiwi, Niken Mela; , Susatyo Yuwono, S.Psi., M.Si, Psi (2017)
The aims of this research is to find the correlation between the perception toward salary with work loyalty, the level of perception toward salary, the level of work loyalty,and the effective contribution of perception toward salary to the work loyalty. The participant of this research are 120 production employees of PT. Djitoe Indonesia Tbk. Surakarta. The sample collection technique in this research is accidental sampling. This research used quantitative method and using measuring scale of perception toward salary and scale of work loyalty. The data analyse technique of this research is correlation of Product Moment from Carl Pearson using SPSS 16 for windows program. By the outcome of data analysis, showed the value of correlation coefficient 0,326 with sig. (p) 0,000 (p < 0,01) it means that there is a significant positive relation between perception toward salary and work loyalty to the employees of PT. Djitoe Indonesia Tbk. Surakarta. The mean empirical (ME) of variable perception toward salary is as big as 33,42 is included in average category, while the mean empirical (ME) of work loyality is as big as 51,94 is included in high category. The effective contribution of perception toward salary with work loyalty is 10,6% so there is 89,4% that influenced by another factors.